Software GeoGebra as a Proposal for Mathematical Modeling Problems - Renata Teófilo de Sousa; Paulo Vítor da Silva Santiago; Francisco Régis Vieira Alves (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Purpose: This study arises from an investigation into the difficulties in understanding Geometry and the mishaps in the interpretation of problems from the Mathematics Olympiads. The objective of this work is to present a didactic proposal that explores the resolution of Olympic issues, developing visualization skills and geometric reasoning with the support of GeoGebra software. Methodology: For this, we used Didactic Engineering as a methodology, in its first two phases - preliminary analysis and a priori analysis - considering that this study is part of an ongoing research. Findings: As a result, we present a didactic proposal that explores two questions of the International Kangaroo Mathematics, describing their resolution based on the assumptions of the Theory of Didactic Situations. Significance: Finally, we hope to contribute to the teaching work in this area and, subsequently, implement these didactic situations in the last two phases of Didactic Engineering, carrying out their experimentation, posterior analysis, and validation.